Impact of COVID-19 on the Prescribing Pattern of Oral Anticoagulants for Atrial Fibrillation After Cardiac Surgery - Dannick Brochu PharmD; Amélie St-Arnaud BPharm, MSc, BCCP; Louis-Étienne Marchand BPharm, MSc, BCCP; Pierre Voisine MD; Julie Méthot PhD (Journal of Cardiovascular Pharmacology and Therapeutics, 2022)
Background: Because of logistic challenges associated with the COVID-19 pandemic, direct oral anticoagulants (DOAC) were favored over warfarin in patients presenting postoperative atrial fibrillation (AF) after cardiac surgery in our institution. Considering the limited evidence supporting the use of DOAC in this context, we sought to evaluate the safety and efficacy of this practice change. Methods: A retrospective study was performed with patients from the Quebec City metropolitan area who were hospitalized at the Institut universitaire de cardiologie et de pneumologie de Québec-Université Laval following cardiac surgery and who required oral anticoagulant (OAC) for postoperative AF. The primary objective was to compare the pre- and peri-COVID-19 period for OAC prescribing patterns and the incidence of thrombotic and bleeding events at 3 months post-surgery. The secondary objective was to compare DOAC to warfarin in terms of thrombotic events and bleeding events. Results: A total of 233 patients were included, 142 from the pre-COVID-19 and 91 from the peri-COVID-19 period, respectively. Both groups had equivalent proportions of preoperative AF (48%) and new-onset postoperative AF (52%). The proportion of patients treated with a DOAC increased from 13% pre-COVID-19 to 82% peri-COVID-19. This change in practice was not associated with a significant difference in the incidence of thrombotic or bleeding events 3 months postoperatively. However, compared to DOAC, warfarin was associated with a higher incidence of major bleeding. Only 1 thrombotic event was reported with warfarin, and none were reported with DOAC. Conclusion: This study suggests that DOAC are an effective and safe alternative to warfarin to treat postoperative AF after cardiac surgery and that this practice can be safely maintained.